Prevalence of psychoactive substance use in pregnant and puerperal women - Karen Barcelos Lopes; Juliane Portella Ribeiro; Alitéia Santiago Dilélio; Amanda Rosário Tavares; Beatriz Franchini; Melissa Hartmann (Universidade Federal de Santa Maria, 2021)
Objective: to investigate the prevalence of psychoactive substance use in pregnant and puerperal women attended at an outpatient clinic in a teaching hospital. Method: A descriptive transversal research with a sample of 174 pregnant and puerperal women. The Alcohol, Smoking and Substance Involvement Screening Test (ASSIST) and a sociodemographic and obstetric-gynecologic survey were utilized in data collection. Data analysis was performed through descriptive statistics. Results: the prevalence of psychoactive substance use among pregnant women was of 28.7% and 1.1% among puerperal women, with alcohol and tobacco as highlights. Tobacco constitutes the substance with greater frequency of use, triggering greater desire/urgency of consummation and a higher rate of intake lowering attempts. Conclusion: the use of psychoactive substances among pregnant and puerperal women constitutes a challenge to public health and for health professionals, eliciting the development of educational actions as well as early identification of these women.